THE HIGH LOW OF THE GULUDAN AND THE PRUNING PERIOD AGAINST THE GROWTH AND RESULTS OF YELLOW POTATO BULBS IN THE KAABUPATEN REJANG LEBONG PLATEAU - Adnan, Adnan; Apriani, Mardia; Suryani, Rini (Corolla International Conference, 2022)
Potatoes (Solanum tuberosum), is one of the many vegetable commodities that are cultivated in the Highlands, including in Rejang Lebong Regency on a plateau of 750 SD 1100 m above sea level. The study was conducted mid-July to December 2019, at the Pat Petulai Rejang Lebong University pilot Garden. The research aims to further the influence of high-low differentiation and the period of pruning the growth and results of yellow potato bulbs. The research method uses the complete random group factorial design (RAKL-F). The high treatment of Guludan (G) of the ground surface is G0 = 0 cm, G1 = 10 cm, G2 = 20 cm, G3 = 30 cm. and second treatment time period of pruning buds (P) after planting ie P0 = without pruning buds, P1 = 25 days after planting, P2 = 30 days, P3 = 35 days. The number of planting populations used in the study was 288 seedlings of potato bulbs The observed variables include: height of the plant, number of main stems, number of shoots, diameter of trunk, heavy weight of the tuber, tuber diameter, number of tubers and dry weight of the tuber. The research results, based on the 5% DMRT test, the high treatment of Guludan 10 cm berbedanyata with another treatment of the number of rods, the diameter of the trunk. The high treatment of Guludan 20 cm, berbedanyata with another treatment of wet weight. The treatment without trimming is not berbedanyata with other treatment of plant height, number of rods. Pruning of 35 days, is distinct from the other treatment of wet weights and the number of bulbs. 5% DMRT test, high combination of Guludan 10 cm with pruning period of 25 days and 35 days, differs in real with other treatment of plant height, number of shoots, number of main stem and diameter of the tuber. A combination of high and 20 cm with a 25 day trimming, not berbedanyata with another combination of treatment of wet weight. The DMRT test is 5%, with no trimming (P0) and high and there is an interaction to the average number of main rods and tuber diameters. Conclusion: The high treatment of Guludan 0, 10 cm, and 20 cm are influential against plant and to the generative period. The treatment without trimming (P0) and 35 days affects the vegetative period, and the generative period. High combination treatment of Guludan 10 cm to 20 cm with pruning period of 35 days, effect on tuber diameter and generaif period. The unpruning treatment is an interaction of vegetative times and the tuber diameter. The treatment without high and high-level and there is no interaction to the number of rods.